2022
DOI: 10.1186/s13063-022-06946-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Internet of Things-based power cycling and neuromuscular training on pain and walking ability in elderly patients with KOA: protocol for a randomized controlled trial

Abstract: Background Osteoarthritis (OA) is a common and highly disabling disease that imposes a heavy burden on individuals and society. Although physical therapy is recommended as an important method to relieve OA symptoms, patients cannot continue treatment after returning home. Research on Internet telerehabilitation for knee osteoarthritis (KOA) can reduce pain and improve patient quality of life, and Internet of Things (IoT)-based telerehabilitation is a new form of delivering rehabilitation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Many researchers found that the pandemic had negative impacts on their cognitive and physical health [18][19][20] . Several studies demonstrated the growing integration of IoT technologies in exercise and rehabilitation programs, offering innovative ways to monitor, motivate, and tailor physical activities to individual needs among older adults 21,22 . Using an innovative digitalized community-based square-stepping exercise program (DC-SSEP) developed by the researchers, this pilot study is among the first studies to evaluate its impacts on cognitive and physical domains among older adults living in a senior facility in the United States who experienced prolonged isolation and had minimal opportunities to interact with others while enjoying group exercise during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers found that the pandemic had negative impacts on their cognitive and physical health [18][19][20] . Several studies demonstrated the growing integration of IoT technologies in exercise and rehabilitation programs, offering innovative ways to monitor, motivate, and tailor physical activities to individual needs among older adults 21,22 . Using an innovative digitalized community-based square-stepping exercise program (DC-SSEP) developed by the researchers, this pilot study is among the first studies to evaluate its impacts on cognitive and physical domains among older adults living in a senior facility in the United States who experienced prolonged isolation and had minimal opportunities to interact with others while enjoying group exercise during the pandemic.…”
Section: Introductionmentioning
confidence: 99%